Design of the illumination system in the field emission Scanning Electron Microscope (SEM) - Mohammed Abdullah Hussein; Faez Ahmed Mohammed (Kirkuk Journal of Science, 2017)
The main goal of This Work is to survey the field emission scanning electron microscope (SEM) to obtain on the optimal design for illumination system. The SEM optical column contains of illumination system that form a focused beam by electrons are released and animated to incident on the specimen surface, this backscattered electrons from the specimen surfaces, finally forming an image. mainly the optical column include a field emission source as the beam source, illumination system, electron control unit, and unit the vacuum. use of a finite element analyses in the design process of the SEM ingredient to be optimally determined. By the analysis we can predict the beam emission characteristics and relevant trajectories were predicted from the analysis of the present work from which a systematic design of the electron optical system is enabled.